2010
DOI: 10.1053/j.ackd.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Polycystic Liver Disease

Abstract: Isolated polycystic liver disease (PCLD) is an autosomal dominant disease with genetic and clinical heterogeneity. Apart from liver cysts, it exhibits few extra-hepatic manifestations and the majority of patients with this condition are asymptomatic or subclinical. However, a small fraction of these patients develop acute liver-cyst-related complications and/or massive cystic liver enlargement, causing morbidity and mortality. Currently, the management for symptomatic PCLD is centered on palliating symptoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 76 publications
0
55
0
2
Order By: Relevance
“…Complications can also cause calcification of cyst walls. Associated dilatation of the intrahepatic and extrahepatic bile ducts may also be found in autosomal dominant polycystic liver disease [3,12].…”
Section: Santiago Et Almentioning
confidence: 99%
See 3 more Smart Citations
“…Complications can also cause calcification of cyst walls. Associated dilatation of the intrahepatic and extrahepatic bile ducts may also be found in autosomal dominant polycystic liver disease [3,12].…”
Section: Santiago Et Almentioning
confidence: 99%
“…Most patients have no symptoms. Imaging studies usually show multiple liver cysts of various sizes, as large as 12 cm, in an enlarged liver [3,12]. Ultrasound images show cysts as anechoic lesions with well-defined thin walls.…”
Section: Santiago Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Qian (2010) [68] reported that isolated polycystic liver disease (PCLD) is an autosomal dominant disease with genetic and clinical heterogeneity. Rabbani et al (2010) [69] reported a case of a renal transplant recipient who suffered an isolated Mycobacterium tuberculosis infection of a native polycystic kidney.…”
Section: Diagnosis and Screeningmentioning
confidence: 99%